A New Challenge in Institutional Education - Multiculturalism in Preschools and Elementary Schools - Imre Lipcsei (Ignatianum University Press, 2019)
The social and cultural environment of kindergartens and schools has experienced considerable changes during the past few decades. This greatly affected teachers as well, since children with a wide range of economic, cultural and family backgrounds bring with them contrasting moral values to preschools or elementary schools. Children of migrant workers, refugees, immigrants lead to increased diversity which requires new competences from teachers. The notion of incorporating multiculturalism in today's schools is beyond question. Therefore education policy should signivcantly prioritize the inclusion of cultural varieties: diterent religions, diverse traditions and customs.